🎉 从330转为WashU帮助手册啦!

Math429
模块
Math429 L14

Lecture 14

Chapter III Linear maps

Assumption: U,V,WU,V,W are vector spaces (over F\mathbb{F})

Matrices 3C

Review

Proposition 3.76

M(Tv)=M(T)M(v)M(Tv)=M(T)M(v)

Theorem 3.78

Let V,WV,W be finite dimensional vector space, and TL(V,W)T\in \mathscr{L}(V,W) then dim range T=column rank(M(T))=rank(M(T))dim\ range\ T=column\ rank (M(T))=rank(M(T))

Proof:

range=Span{Tv1,...,Tvn}range=Span\{Tv_1,...,Tv_n\} compare to Span{M(T),1,...,M(T),n}=Span{M(T)M(v1),...,M(T)M(vn)}=Span{M(Tv1),...,M(Tvn)}Span\{M(T)_{\cdot,1},...,M(T)_{\cdot, n}\}=Span\{M(T)M(v_1),...,M(T)M(v_n)\}=Span\{M(Tv_1),...,M(Tv_n)\}

Since MM is a isomorphism, then the theorem makes sense.

Change of Basis

Definition 3.79, 3.80

The identity matrix

I=(1.001)I=\begin{pmatrix} 1.& 0\\ 0& '1\\ \end{pmatrix}

The inverse matrix of an invertible matrix AA denoted A1A^{-1} is the matrix such that

AA1=I=A1AAA^{-1}=I=A^{-1}A

Question: Let u1,...,unu_1,...,u_n and v1,...,vnv_1,...,v_n be two bases for VV. What is M(I,(u1,...,un),(v1,...,vn)),IL(V)M(I,(u_1,...,u_n),(v_1,...,v_n)),I\in \mathscr{L}(V)

Proposition 3.82

Let u1,...,unu_1,...,u_n and v1,...,vnv_1,...,v_n be bases of VV, then M(I,(u1,...,un),(v1,...,vn)),IL(V)M(I,(u_1,...,u_n),(v_1,...,v_n)),I\in \mathscr{L}(V) and M(I,(v1,...,vn),(u1,...,un)),IL(V)M(I,(v_1,...,v_n),(u_1,...,u_n)),I\in \mathscr{L}(V) are inverse to each other.

Proof:

M(I,(u1,...,un),(v1,...,vn)),IL(V)M(I,(v1,...,vn),(u1,...,un))=M(I,(u1,...,un),(u1,...,un))M(I,(u_1,...,u_n),(v-1,...,v_n)),I\in \mathscr{L}(V) M(I,(v-1,...,v_n),(u_1,...,u_n))=M(I,(u_1,...,u_n),(u_1,...,u_n))

Theorem 3.84 Change of Basis

Let u1,...,unu_1,...,u_n and v1,...,vnv_1,...,v_n be two bases for VV and TL(v),A=M(T,(u1,...,un)),B=M(T,(v1,...,vn)),C=M(I,(u1,...,un),(v1,...,vn))T\in \mathscr{L}(v), A=M(T,(u_1,...,u_n)), B=M(T,(v_1,...,v_n)), C=M(I,(u_1,...,u_n),(v_1,...,v_n)), then A=C1BCA=C^{-1}BC

Theorem 3.86

Let TL(v)T\in \mathscr{L}(v) be an invertible linear map, then M(T1)=M(T)1M(T^{-1})=M(T)^{-1}

Products and Quotients of Vector Spaces 3E

Goals: To construct vectors spaces from other vector spaces.

Definition 3.87

Suppose V1,...,VmV_1,...,V_m vectors spaces over some field F\mathbb{F}, then the product is given by

V1×...×Vn={(v1,v2,...,vn)v1V1,v2V2,...,vnVn}V_1\times ...\times V_n=\{(v_1,v_2,...,v_n)\vert v_1\in V_1, v_2\in V_2,...,v_n\in V_n\}

with addition given by

(v1,...,vn)+(u1,...,un)=(v1+u1,...,vn+un)(v_1,...,v_n)+(u_1,...,u_n)=(v_1+u_1,...,v_n+u_n)

and scalar multiplication

λ(v1,...,vn)=(λv1,...,λvn),λF\lambda (v_1,...,v_n)=(\lambda v_1,...,\lambda v_n),\lambda \in \mathbb{F}

Theorem 3.89

If v1,...,vnv_1,...,v_n are vectors paces over F\mathbb{F} then V1×...×VnV_1\times ...\times V_n is a vector space over F\mathbb{F}

Example:

V=P2(R)×R2={(p,v)pP2(R),vR2}={(a0+a1x+a2x,(b,c))a0,a1,a2,b,cR}V=\mathscr{P}_2(\mathbb{R})\times \mathbb{R}^2=\{(p,v)\vert p\in \mathscr{P}_2(\mathbb{R}), v\in \mathbb{R}^2\}=\{(a_0+a_1x+a_2x,(b,c))\vert a_0,a_1,a_2,b,c\in \mathbb{R}\}

A basis for VV would be (1,(0,0)),(x,(0,0)),(x2,(0,0)),(0,(1,0)),(0,(0,1))(1,(0,0)),(x,(0,0)),(x^2,(0,0)),(0,(1,0)),(0,(0,1))

Theorem 3.92

dim(V1×...×Vn)=dim(V1)+...+dim(Vn)dim(V_1\times ...\times V_n)=dim(V_1)+...+dim(V_n)

Sketch of proof:

take a basis for each VkV_k, make them vectors in the product then combine the entire list of vector to be basis.

Example:

R2×R3={((a,b),(c,d,e))a,b,c,d,eR}\mathbb{R}^2\times \mathbb{R}^3=\{((a,b),(c,d,e))\vert a,b,c,d,e\in \R\}

R2×R3R5,((a,b),(c,d,e))(a,b,c,d,e)\mathbb{R}^2\times \mathbb{R}^3\cong \mathbb{R}^5,((a,b),(c,d,e))\mapsto(a,b,c,d,e)

Theorem 3.93

Let V1,...,VmVV_1,...,V_m\subseteq V, define Γ:V1×...×VmV1+...+Vm\Gamma: V_1\times...\times V_m\to V_1+...+V_m. Γ(v1,...,vn)=v1+...+vn\Gamma(v_1,...,v_n)=v_1+...+v_n then Γ\Gamma is always surjective. And it is injective if and only if V1+...+VmV_1+...+V_m is a direct sum.

Sketch of the proof:

injective     null T{(0,...,0)}    \iff null\ T\{ (0,...,0) \} \iff the only way to write 0=v1,...,vm0=v_1,...,v_m is v1=...=vn=0    v_1=...=v_n=0 \iff then V1+...+VmV_1+...+V_m is a direct sum

Theorem 3.94

V1+...+VmV_1+...+V_m is a direct sum if and only if dim(V1+...+Vm)=dim(V1)+...+dim(Vm)dim(V_1+...+V_m)=dim(V_1)+...+dim(V_m)

Proof:

Use Γ\Gamma above is an isomorphism     \iff V1+...+VmV_1+...+V_m is a direct sum

Use Γ\Gamma above is an isomorphism     dim(V1+...+Vm)=dim(V1)+...+dim(Vm)\implies dim(V_1+...+V_m)=dim(V_1)+...+dim(V_m)